Response of nutrients level and pruning intensity on vegetative growth of Apple ber (Ziziphus mauritiana L.) under sodic soil condition - Hemant Kumar; Niranjan Singh; Atul Yadav; Amit Mishra; Abhishek Sonkar; S. K. Verma; Bhanu Pratap (The Bioscan, 2025)
The experiment was carried out at the Main Experiment Station, Department of Fruit Science, Acharya Narendra Deva University of Agriculture and Technology, Kumarganj, Ayodhya, U.P., during the years 2023-24 to 2024-25. To find out the response of nutrient level and pruning intensity on vegetative growth of Apple ber (Ziziphus mauritiana L.) under sodic soil conditions. reproductive growth, and yield of Apple ber (Ziziphus mauritiana L.) under sodic soil conditions. The treatments investigated the effects of varying pruning intensities 4 buds, 6 buds, and 8 buds combined with foliar application of nutrient, time of spraying July-August (Pre-flowering stage), and Oct. (Fruit set stage) application, including boric acid, and zinc sulphate, both were used at 0.2%, 0.4% concentration, and control. The treatment interaction with P4: 8 buds pruning intensity and Nutrient RDF NPK 19: 19: 19 + boron 0.2% and zinc 0.4% (P4×N3) demonstrated the most significant increase in vegetative growth, showing such as shoot length cm (278.49 and 280.79) in 2023-24 and 2024-25 respectively. The study provides valuable insights into optimizing the Ber plant vegetative growth through targeted pruning and nutrient management practices.